Is green transportation efficiency the panacea for alleviating carbon lock-in? The case of China - Congyu Zhao; Kun Wang (Transport Economics and Management)
The development of green transportation is crucial for creating a low-carbon roadmap in the transportation sector. We calculate the efficiency of green transportation in China and then examine its effect on carbon lock-in. The asymmetric nexus between green transportation efficiency and carbon lock-in is investigated, and the moderating and mediating effects are also examined. Our results indicate that (1) green transportation efficiency is effective in reducing carbon lock-in and promoting a low-carbon transition; (2) The relationship between green transportation efficiency and carbon lock-in is asymmetric, with green transportation efficiency having a stronger effect in areas with lower levels of carbon lock-in. (3) Environmental regulation can contribute to the eradication of carbon lock-in and strengthen the effect of green transportation efficiency, showing significant a moderating effect. (4) Green transportation efficiency indirectly affects carbon lock-in by promoting energy consumption efficiency and renewable energy development.